2006
DOI: 10.1111/j.1439-0434.2006.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid RT‐PCR Test for the Detection of Peach Latent Mosaic Viroid, Pear Blister Canker Viroid, Hop Stunt Viroid and Apple Scar Skin Viroid in Fruit Trees from Tunisia

Abstract: A reverse transcription polymerase chain reaction was developed to investigate the occurrence of Ôpeach latent mosaic viroidÕ (PLMVd), Ôpear blister canker viroidÕ (PBCVd), Ôhop stunt viroidÕ (HSVd) and Ôapple scar skin viroidÕ (ASSVd) on fruit trees (peach, pear, almond and apple) in Tunisia. The test was initially performed with total RNA preparations from selected isolates and then applied to total RNA preparations from leaf or bark tissues of fruit trees collected in the north of Tunisia and the Sahel. PLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The samples were taken from trees in different regions of Tunisia: Ben Arous, Bizerte, Manouba, Nabeul, and Zaghouane in the north, Kairouane in the center, and Mahdia in the Sahel. Initially, PLMVd was detected by RT-PCR in all samples (Fekih Hassen et al, 2006). The selection of the primers was achieved according to a previous sequencing study (Ambros et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were taken from trees in different regions of Tunisia: Ben Arous, Bizerte, Manouba, Nabeul, and Zaghouane in the north, Kairouane in the center, and Mahdia in the Sahel. Initially, PLMVd was detected by RT-PCR in all samples (Fekih Hassen et al, 2006). The selection of the primers was achieved according to a previous sequencing study (Ambros et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…PLMVd-infected leaves were collected from 31 peach trees belonging to 14 different cultivars, 2 almond trees, and 1 pear tree growing in different regions of Tunisia: the north (Ben Arous, Bizerte, Manouba, Nabeul and Zaghouane), the center (Kairouane), and the Sahel (Mahdia). RNA was extracted from the leaves as reported previously (Fekih Hassen et al, 2006).…”
Section: Viroid Sourcesmentioning
confidence: 99%
“…Although a single PBCVd infection was detected from a pear tree in a commercial orchard in Colorado, no naturally occurring mixed infections with any of these four viroids have been detected in our samples. Mixed infections of PBCVd and Hop stunt viroid (HSVd) or HSVd and Peach latent mosaic viroid have been reported in pear trees (Fekih Hassen et al 2006), and several combinations of mixed viroid infections were reported from apple and pear trees in Greece (Kaponi et al 2010a). In this study, all four viroids were detected in pears trees that were inoculated with ADFVd, AFCVd, ASSVd, and PBCVd; however, PBCVd could not be detected by mRT-PCR in any of three seedling apple trees inoculated with all four viroids.…”
Section: Discussionmentioning
confidence: 97%
“…So, using a previously published RT‐PCR protocol (Fekih Hassen et al., 2006), a large survey of PLMVd incidence was undertaken in eight peach cultivars in the main production areas of Tunisia. During this survey, data such as the geographical origin, cultivar and rootstock identity and origin and age of the trees were collected.…”
Section: Introductionmentioning
confidence: 99%